Media coverage of the 2018 African Youth Games in its third edition in Algeria - An analytical study of Al-Nahar newspaper - lawsyn, sulayman (ALBAHITH ALALAMI, 2019)
This research revolves around the study of sports press coverage to the third African Youth Games that took place in Algeria from 19 to 28 July 2018. The games featured approximately 3000 athletes from 54 countries who competed in 27 sports. Five sports were qualified for the Youth Olympic Games in Argentina. The aim of this study was to analyze the content of the Algerian newspaper Ennahar El-Djadid by focusing on the discussions of various sports activities during the event. Thus, the descriptive approach and content analysis method were adopted for this research. They were used to highlight the newspaper's interest in this sports phenomenon. The chosen study samples were ten issue numbers of Ennahar El-Djadid newspaper